Kepemimpinan Transformasional dan Budaya Sekolah dalam Meningkatkan Kinerja Guru: Peran Mediasi Motivasi Kerja - Suharjo; Budi Valianto; Darwin; Eka Daryanto; Aman Simare-Mare; Mesnan; Haidir (Universitas Negeri Medan, 2026)
This study aims to analyze the influence of transformational leadership of school principals and school culture on teacher performance through teacher work motivation in high schools in Medan City. The research uses a quantitative approach with a survey method. The research population was 180 teachers with a sample of 124 respondents. The research instrument used a Likert scale questionnaire. Data analysis uses path analysis. The results of the study show that transformational leadership and school culture have a positive effect on teachers' work motivation and teacher performance. Work motivation has been shown to mediate the relationship between transformational leadership and school culture on teacher performance. The findings of the study confirm that improving teacher performance requires strong transformational leadership of the principal, a positive school culture, and high teacher work motivation.